Prevalence, Antimicrobial Resistance, and Genetic Diversity of Listeria spp. Isolated from Raw Chicken Meat and Chicken-Related Products in Malaysia - Chin, Pui San; Ang, Geik Yong; Yu, Choo Yee; Tan, Eng Lee; Tee, Kok Keng; Yin, Wai Fong; Chan, Kok Gan; Tan, Geok Yuan Annie (International Association for Food Protection, 2018)
Listeria spp. are ubiquitous in nature and can be found in various environmental niches such as soil, sewage, river water, plants, and foods, but the most frequently isolated species are Listeria monocytogenes and Listeria innocua. In this study, the presence of Listeria spp. in raw chicken meat and chicken-related products sold in local markets in Klang Valley, Malaysia was investigated. A total of 44 Listeria strains (42 L. innocua and 2 L. welshimeri) were isolated from 106 samples. Antibiotic susceptibility tests of the L. innocua strains revealed a high prevalence of resistance to clindamycin (92.9%), ceftriaxone (76.2%), ampicillin (73.8%), tetracycline (69%), and penicillin G (66.7%). Overall, 31 L. innocua and 1 L. welshimeri strain were multidrug resistant, i.e., nonsusceptible to at least one antimicrobial agent in three or more antibiotic classes. The majority of the L. innocua strains were placed into five AscI pulsogroups, and overall 26 distinct AscI pulsotypes were identified. The detection of multidrug-resistant Listeria strains from different food sources and locations warrants attention because these strains could serve as reservoirs for antimicrobial resistance genes and may facilitate the spread and emergence of other drug-resistant strains.